Análise de genótipos fimA de Porphyromonas gingivalis e de polimorfismos genéticos em indivíduos com periodontite - Rodrigues, Richelle Soares (2019)
Periodontal destruction is related to the presence of periodontopathogenic microbiota and to the susceptibility of the patient to the disease. The objective of this study was to assess the presence of the periodontopathogen Porphyromonas gingivalis and its fimA genotypes in subgingival biofilm of patients with periodontitis in its most advanced forms, as well as the presence of genetic polymorphisms in CDKN2BAS and GLT6D1 genes. One hundred patients with periodontitis stages III and IV grades B and C and 61 healthy patients were evaluated. Clinical examination included gingival index, bleeding at probing, depth of catheterization and level of clinical insertion. Subgengival biofilm samples were evaluated through PCR for microbiological analysis and saliva samples were analyzed by RT-PCR for detection of the genetic polymorphisms. The prevalence of P. gingivalis was 61.96% and it was more prevalente in grade C periodontitis patients (p=0.048), in patients with greater probing depth (p<0.001), clinical attachment level (p<0.001) and bleending on probing (p=0.01), and in sites with greater periodontal destruction (p=0.01). FimA II genotype was more prevalent in patients with greater mean probing depth (p=0.04) and greater proportion of bleeding sites (p=0.006). None of the genetic polymorfisms studied showed a significant association to periodontitis patients when compared to healthy subjects, nor when compared to grades B and C periodontits patients. In conclusion, in the sample of Brazilians with periodontitis stages III and IV grades B and C, the prevalence of P. gingivalis was higher in grade C patients and in those with sites with greater periodontal destruction, the presence of its fimA II genotype was higher in those with greater mean probing depth and proportion of bleeding sites, but they were not associated with polymorphisms in the CDKN2BAS and GLT6D1 genes in the brazilian population studied.